1998
DOI: 10.1086/515375
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Acyclovir‐Resistant Herpes Simplex in an Immunocompromised Patient: Can Strain Differences Compensate for Loss of Thymidine Kinase in Pathogenesis?

Abstract: To investigate how acyclovir-resistant (ACVr) herpes simplex virus (HSV) evades drug therapy and causes disease, HSV-1 isolates from a bone marrow transplant (BMT) patient were studied. The patient developed ACVr disease after an initial BMT and, following a second BMT, reactivated ACVr HSV despite high-dose acyclovir prophylaxis. ACVr isolates from each episode contained the same point mutation in the viral thymidine kinase (tk) gene, documenting the emergence, latency, and reactivation of this mutant. The mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 36 publications
5
55
1
Order By: Relevance
“…It was previously reported that virus reactivated from approximately 25% of trigeminal ganglia latently infected with the clinical isolate 615.9 and that the viruses that reactivated had a TK L phenotype (18). However, a loss of dependence on TK for reactivation has been shown for a different clinical isolate (16). The latter observation called into question the importance of the TK L phenotype in the reactivation of 615.9.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It was previously reported that virus reactivated from approximately 25% of trigeminal ganglia latently infected with the clinical isolate 615.9 and that the viruses that reactivated had a TK L phenotype (18). However, a loss of dependence on TK for reactivation has been shown for a different clinical isolate (16). The latter observation called into question the importance of the TK L phenotype in the reactivation of 615.9.…”
Section: Resultsmentioning
confidence: 98%
“…Virus 294dlTK (Fig. 1) was generated following cotransfection of p294⌬TK with infectious DNA derived from 294.1, as previously described (16). This procedure involved one round of purification under 120 M ACV, followed by three rounds of plaque purification in the absence of the drug.…”
Section: Cells and Viruses African Green Monkey Kidney (Vero) And Tkmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the mutation suggested to confer increased heterogeneity is the same as that reported to permit the low levels of TK via ribosomal frameshifting (27). There is also evidence for another mechanism in which the virus appears to circumvent any requirement for TK in pathogenesis, possibly by a compensatory mutation elsewhere in the viral genome (15). In this study we have attempted to avoid the influence of the third mechanism by reconstituting the mutation into a laboratory strain, KOS, which has an absolute requirement for TK for reactivation from latency.…”
mentioning
confidence: 99%
“…Foscarnet does not require the viral thymidine kinase for its activity and is currently the only approved treatment for ACV-resistant HSV infections. 2,11 Failure of foscarnet has previously been described in HIV infections and in hematological malignancies. 2 Cross-resistance to foscarnet suggests either an alteration in the DNA polymerase or a combination of separate HSV drug-resistant populations.…”
Section: Discussionmentioning
confidence: 99%